2012
DOI: 10.1016/j.jnutbio.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-gallate stimulates NF-E2-related factor and heme oxygenase-1 via caveolin-1 displacement

Abstract: Flavonoids, such as the tea catechin epigallocatechin-gallate (EGCG), can protect against atherosclerosis by decreasing vascular endothelial cell inflammation. Heme oxygenase (HO-1) is an enzyme that plays an important role in vascular physiology, and its induction may provide protection against atherosclerosis. HO-1 can be compartmentalized in caveolae in endothelial cells. Caveolae are plasma microdomains important in vesicular transport and the regulation of signaling pathways associated with the pathology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 36 publications
3
37
0
1
Order By: Relevance
“…It is reported that a 67-kDa laminin receptor (67LR), as the cell surface EGCG receptor, may be involved in mediating these actions of EGCG (22)(23)(24)(25). Moreover, EGCG is also believed to exert an Epigallocatechin-3-gallate prevents TNF-α-induced NF-κB activation thereby upregulating ABCA1 via the Nrf2/Keap1 pathway in macrophage foam cells anti-atherosclerotic effect via anti-inflammatory and metabolic regulation activities (26,27). It has also been proposed that EGCG could restrain inflammatory cytokines, such as TNF-α and IL-1β, through blocking NF-κB pathway, and nuclear factor E2-related factor 2 (Nrf2) might be involved in this process (18,28,29).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that a 67-kDa laminin receptor (67LR), as the cell surface EGCG receptor, may be involved in mediating these actions of EGCG (22)(23)(24)(25). Moreover, EGCG is also believed to exert an Epigallocatechin-3-gallate prevents TNF-α-induced NF-κB activation thereby upregulating ABCA1 via the Nrf2/Keap1 pathway in macrophage foam cells anti-atherosclerotic effect via anti-inflammatory and metabolic regulation activities (26,27). It has also been proposed that EGCG could restrain inflammatory cytokines, such as TNF-α and IL-1β, through blocking NF-κB pathway, and nuclear factor E2-related factor 2 (Nrf2) might be involved in this process (18,28,29).…”
Section: Introductionmentioning
confidence: 99%
“…M marker, B unstimulated cells, C PMA plus A23187-stimulated cells promising treatment and prevention of inflammation-related conditions. EGCG is the most abundant catechin in green tea (Zheng et al 2011). We therefore investigated the natural product-based compound EGCG as a natural product-based anti-inflammatory agent.…”
Section: Discussionmentioning
confidence: 99%
“…1) (Zheng et al 2011). EGCG has various effects such as anti-arthritic, anti-inflammatory, and anti-oxidant effects (Ahemd et al 2008;Wheeler et al 2004a;Rah et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, EGCG increased the level of HO-1 expression by Nrf-2 activation in endothelial cells, resulting in the passage of caveolin-1 from the plasma membrane to the cytosol, accumulating in the caveolae-regulating signaling pathways associated with vascular disease pathology [60]. Accordingly, EGCG may reduce endothelial inflammation and protect against atherosclerosis [61]. EGCG also showed a protective effect against oxidative stress-induced cerebral ischemia through Nrf2/ARE activation [62].…”
Section: Epigallocatechin Gallatementioning
confidence: 98%